Manajemen risiko dalam perspektif maqashid syariah pada lembaga keuangan islam - Rohmah, Sabana Nur (Maliki Interdisciplinary Journal, 2026)
A crucial aspect in maintaining the stability of Islamic financial institutions is risk management, particularly in terms of risks related to financing, operations, and Sharia compliance. This study examines risk management from the perspective of maqashid sharia and its application to Islamic financial institutions. The method used is a descriptive qualitative approach, which is used to examine literature from various scientific journals. The results show that maqashid sharia provides a broad risk management framework with an emphasis on protecting five main elements: religion, life, mind, lineage, and property. In practice, customer socioeconomic factors, such as age, education, and environment, influence risks such as non-performing financing (NPF). In addition, maqashid sharia is also used in Islamic microfinance institutions, which aim to improve community welfare through fair and transparent financing. However, the implementation of maqashid-based risk management faces challenges such as the dominance of conventional systems and limitations in integrating Sharia values. Therefore, to ensure that Islamic financial institutions operate effectively, ideas on risk management must be strengthened to support the public interest. In practice, such risks as non-performing financing (NPF) are affected.